Тhe educational impact of information technology on personal development of pupils - Коваль, Марина (Pedagogy of Higher and Secondary Education, 2015)
Koval M. M Тhe educational impact of information technology on personal development of pupils. The article highlights the problem of preparing the younger generation to a full, productive life in the development of new level school using new information technologies and their use in the educational process as a means to preserve the originality and uniqueness of every child ready for self-disclosure. The introduction of new information technologies in the educational sector , education of the individual in the modern world of developing society with full access to information from unrestricted age characteristics is analysed.